2021
DOI: 10.7554/elife.55081
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional networks associated with social bonding in monogamous voles

Abstract: Previous studies have related pair-bonding in Microtus ochrogaster, the prairie vole, with plastic changes in several brain regions. However, the interactions between these socially relevant regions have yet to be described. In this study, we used resting-state magnetic resonance imaging to explore bonding behaviors and functional connectivity of brain regions previously associated with pair-bonding. Thirty-two male and female prairie voles were scanned at baseline, 24 hr, and 2 weeks after the onset of cohabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 111 publications
1
12
0
Order By: Relevance
“…Our partner network features correlations across all of these regions as well. Furthermore, a recent fMRI study in voles reported that functional connectivity of a neural network correlates with partner-directed affiliation (López-Gutiérrez et al, 2021). Our results show similar regional coactivity as well as modular organization suggesting that such interconnected regions may be correlated with affiliative behaviors (e.g., huddling) and rewardprocessing (e.g., mating).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our partner network features correlations across all of these regions as well. Furthermore, a recent fMRI study in voles reported that functional connectivity of a neural network correlates with partner-directed affiliation (López-Gutiérrez et al, 2021). Our results show similar regional coactivity as well as modular organization suggesting that such interconnected regions may be correlated with affiliative behaviors (e.g., huddling) and rewardprocessing (e.g., mating).…”
Section: Discussionsupporting
confidence: 76%
“…Prior research has employed graph theory to analyze large datasets across a wide array of disciplines including organic chemistry, public transportation, finance, etc., (Garcia-Domenech et al, 2008;Derrible and Kennedy, 2009;Quintero et al, 2013;Qiang and Fan, 2016). In addition, several studies have demonstrated functional connectivity associated with social recognition (Tanimizu et al, 2017), aggression (Teles et al, 2015), mating (Johnson et al, 2016;Kabelik et al, 2018), and positive social interactions (Rilling et al, 2018;López-Gutiérrez et al, 2021). We have used a graph theory approach to generate network models of functional connectivity between multiple brain regions.…”
Section: Neural Network Analysis Using Graph Theorymentioning
confidence: 99%
“…For many years, the prairie vole has served as a model for investigating the neural mechanisms of social behavior [Johnson and Young, 2015;Carter and Perkeybile, 2018;Madrid et al, 2020;López-Gutiérrez et al, 2021;Tripp et al, 2021]. These studies have provided a foundation upon which an understanding of how the cellular and molecular processes that shape cognition can be built.…”
Section: Cellular and Molecular Level Effectsmentioning
confidence: 99%
“…Microtus voles have become an established system for studying mammalian social structures, reproductive decision‐making, and social behavior. In particular, prairie voles ( M. ochrogaster ) are best known for their impact on understanding the behavioral and neurobiological mechanisms associated with pair bonding and social monogamy 28,29,34–36 . The greater vole study system is particularly powerful because closely related species differ in their levels of social organization, mating systems, and propensity to form social bonds, even though they often experience similar ecological pressures in nature 37–40 .…”
Section: Prairie Volesmentioning
confidence: 99%